Relative efficiency of health provision: a DEA approach with non-discretionary inputs - Afonso, António (2006)
We estimate a semi-parametric model of health production process using a two-stage approach for OECD countries. By regressing data envelopment analysis output efficiency scores on non-discretionary variables, both using Tobit analysis and a single and double bootstrap procedure, we show that inefficiency is strongly related to GDP per head, the education level, and health behaviour such as obesity and smoking habits. The used bootstrapping procedure corrects likely biased DEA output scores taking into account that environmental variables are correlated to output and input variables.